Anthropology and the cognitive challenge - Bloch, Maurice (New departures in anthropology., 2012)
In this provocative new study one of the world's most distinguished anthropologists proposes that an understanding of cognitive science enriches, rather than threatens, the work of social scientists. Maurice Bloch argues for a naturalist approach to social and cultural anthropology, introducing developments in cognitive sciences such as psychology and neurology and exploring the relevance of these developments for central anthropological concerns: the person or the self, cosmology, kinship, memory and globalisation. Opening with an exploration of the history of anthropology, Bloch shows why and how naturalist approaches were abandoned and argues that these once valid reasons are no longer relevant. Bloch then shows how such subjects as the self, memory and the conceptualisation of time benefit from being simultaneously approached with the tools of social and cognitive science. Anthropology and the Cognitive Challenge will stimulate fresh debate among scholars and students across a wide range of disciplines.